Digital Service System Implementation Based on Self-Circulation on UPT Perpustakaan of Universitas Jambi - Zurweni; Yusnidar (ENCRYPTION: Journal of Information And Technology, 2025)
Central Library (UPT Perpustakaan) of the Universitas Jambi to improve quality in accordance with the needs of the user community or users is to provide maximum service with strategies and systems that make it easier and effective and efficient. This study aims to determine the quality of the UPT Library of the University of Jambi from the aspect of service to users, especially in digital self-service.  Specifically for circulation services, the UPT Library of the University of Jambi has developed its system by facilitating through additions, namely: Digital-based Independent Circulation Service using a PC or a special computer device, separate from other PCs. This service is a development of the circulation service that exists in the SLiMS UPT application of the University of Jambi Library which has been used since 2015. This research method is a quantitative and qualitative method (mixed method), using Concurrent Triangulation.